PREFERENSI MASYARAKAT MENABUNG DI BANK SYARIAH - Muhammad Iryanto; Rusandry Rusandry (Institut Agama Islam Negeri (IAIN) Ternate, 2022)
People's preference for saving in islamic banks can be determined by how much they know or understand about islamic banks and services, as well as how easily they can access islamic banking, and how much this influences their interest in Bacan District. Multiple linear regression has been used to determine the impact of knowledge on people's interest in saving money at islamic banks there. The findings revealed that the knowledge component (P1), which had a probability value of 0.00%, had a substantial impact. The study's findings on the service variable (P2) indicate that there is a lack of public interest in saving in islamic banks, with a likelihood value of 0.87%. The findings disprove the idea that low public interest in saving at islamic banks is a result of poor service. According to earlier research by Maysaroh (2014), location factors have a significant impact on customers' decisions, however the impact is not very strong. In contrast to earlier studies, the findings of which are invariably significant, this study. The location variable (P3) had no statistically significant impact. Despite being easily accessible and including security indications and location techniques, P3 remains the most prominent signal. Additionally, islamic banks must make islamic banking systems and products available to the general public in order to gauge that population's interest in islamic banks. Keywords: Interests; Islamic Banking; Bacan.